Refining diagnostic microRNA signatures by whole-miRNome kinetic analysis in acute myocardial infarction - Heilmeier, Britta; Frese, Karen S.; Kloos, Wanda; Kayvanpour, Elham; Sedaghat-Hamedani, Farbod; Hassel, Sarah; Marquart, Sabine; Giannitsis, Evangelos; Hardt, Stefan; Katus, Hugo; Meder, Benjamin (Clinical chemistry, 2013)
BACKGROUND: Alterations in microRNA (miRNA) expression patterns in whole blood may be useful biomarkers of diverse cardiovascular disorders. We previously reported that miRNAs are significantly dysregulated in acute myocardial infarction (AMI) and applied machine-learning techniques to define miRNA subsets with high diagnostic power for AMI diagnosis. However, the kinetics of the time-dependent sensitivity of these novel miRNA biomarkers remained unknown. METHODS: To characterize temporal changes in the expressed human miRNAs (miRNome), we performed here the first whole-genome miRNA kinetic study in AMI patients. We measured miRNA expression levels at multiple time points (0, 2, 4, 12, 24 h after initial presentation) in patients with acute ST-elevation myocardial infarction by using microfluidic primer extension arrays and quantitative real-time PCR. As a prerequisite, all patients enrolled had to have cardiac troponin T concentrations <50 ng/L on admission as measured with a high-sensitivity assay. RESULTS: We found a subset of miRNAs to be significantly dysregulated both at initial presentation and during the course of AMI. Additionally, we identified novel miRNAs that are dysregulated early during myocardial infarction, such as miR-1915 and miR-181c*. CONCLUSIONS: The present proof-of-concept study provides novel insights into the dynamic changes of the human miRNome during AMI.
Previously published online
Gesehen am 09.10.2018